Handbook of Clinical Sociology
XVI, 437 p.
Keywords: Clinical sociology is an action-oriented field that seeks to prevent, reduce, or resolve the seemingly overwhelming number of social problems confronting modern society. In an extensive revision of the first edition of this classic text and reference, published by Plenum in 1990, the editors have assembled a distinguished roster of contributors to address such topics as theory and practice; intervention at various levels of social organization; specific kinds of sociological practice; social problems; and the process of becoming a clinical sociologist.